Maximising relational capabilities and minimising restrictive practices in acute mental health units: the Safe Steps for De-escalation evaluation - Daguman, Esario I V; Yoxall, Jacqui; Lakeman, Richard; Hutchinson, Marie (Frontiers in Psychiatry, 2025)
ObjectivesDe-escalation is widely endorsed as an intentional strategy to replace and reduce restrictive practices in acute mental health units. However, high-quality evidence for its effective implementation remains limited. In response, a pragmatic, complexity-informed evaluation was undertaken to generate empirical support for the impact of an intervention, Safe Steps for De-escalation, on restrictive practices. The intervention centres on a four-step framework for therapeutic responding, with implementation supported by co-designed training and restrictive practice reviews.MethodsA mixed concurrent control study was conducted in three adult inpatient units in New South Wales, Australia, from March 2023 to April 2025. A priori weighted linear, linear mixed-effects, and generalised linear mixed-effects models were fitted between and within groups, to assess the impact of the intervention on restrictive practice events, including seclusion, physical restraint, as-needed intramuscular psychotropics, event duration, and physical injury. A priori hierarchical cluster analysis and between-cluster comparison were used to examine the most active de-escalation response components and any associated concurrent supplementary strategies contributing to the overall impact.ResultsCompared to three control sites, implementation sites had a lower total restrictive practice event rate (incidence rate ratio [IRR] = 0.65, 95% CI [0.60, 0.69], p <.001) over a twelve-month intervention period. At a granular level, implementation sites had lower IRRs for seclusion and as-needed intramuscular psychotropics than controls; however, within-group rates fluctuated over the year. Two clusters of de-escalation responses and additional supplementary strategies (including stimulus reduction, music, and one-on-one staff time) were noted. The differential associations between clusters and the outcomes were insignificant.ConclusionDespite mixed results, the evaluation offers support that structured therapeutic responding helps minimise restrictive practices, without evidence suggesting a substitution of one form of coercion for another.